Trade and Currency Weapons - Agnes Benassy-Quere; Matthieu Bussière; Pauline Wibaux (Center for Economic Studies and ifo Institute (CESifo), 2018)
The debate on trade wars and currency wars has re-emerged since the Great recession of 2009. We study the two forms of non-cooperative policies within a single framework. First, we compare the elasticity of trade flows to import tariffs and to the real exchange rate, based on product level data for 110 countries over the 1989-2013 period. We find that a 1 percent depreciation of the importer's currency reduces imports by around 0.5 percent in current dollar, whereas an increase in import tariffs by 1 percentage point reduces imports by around 1.4 percent. Hence the two instruments are not equivalent. Second, we build a stylized short-term macroeconomic model where the government aims at internal and external balance. We find that, in this setting, monetary policy is more stabilizing for the economy than trade policy, except when the internal transmission channel of monetary policy is muted (at the zero-lower bound). One implication is that, in normal times, a country will more likely react to a trade “aggression” through monetary easing rather than through a tariff increase. The result is reversed at the ZLB.
Keywords: F13; F14; F31; F60; 330; tariffs; exchange rates; trade elasticities; protectionism